2006
DOI: 10.1182/blood-2005-05-2125
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of oncogenic ALK is a viable therapeutic approach for anaplastic large-cell lymphomas

Abstract: IntroductionAnaplastic large-cell lymphomas (ALCLs) represent a subset of neoplasms with distinctive genetic defects that are immunophenotypically characterized by the sustained expression of CD30. 1 In the late 1980s several groups described the unique association of the t(2;5)(p23;q35) chromosome translocation with ALCL. However, the corresponding genes were discovered several years later by Morris and colleagues. 2 In the t(2;5)(p23;q35) translocation the ALK (anaplastic lymphoma kinase) gene on chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 51 publications
2
116
0
Order By: Relevance
“…The presence of EML-ALK fusion in NSCLC was confirmed in a number of subsequent studies (14)(15)(16)(17)(18); however, it has not yet been detected in other carcinomas, including breast and colorectal (19,20). A number of EML4-ALK fusion variants have been identified up to date (12,18,(20)(21)(22)(23); all of them involve an almost identical portion of ALK (exons [20][21][22][23][24][25][26][27][28][29] The constitutive kinase activity of ALK is essential for proliferation of ALCL cells and its inactivation represents a feasible therapeutic approach for the treatment of ALCL (24). The intact ALK kinase domain within EML4-ALK possesses marked transforming as well as oncogenic activity in vitro and in vivo, respectively (12,21,25).…”
Section: Introductionmentioning
confidence: 80%
“…The presence of EML-ALK fusion in NSCLC was confirmed in a number of subsequent studies (14)(15)(16)(17)(18); however, it has not yet been detected in other carcinomas, including breast and colorectal (19,20). A number of EML4-ALK fusion variants have been identified up to date (12,18,(20)(21)(22)(23); all of them involve an almost identical portion of ALK (exons [20][21][22][23][24][25][26][27][28][29] The constitutive kinase activity of ALK is essential for proliferation of ALCL cells and its inactivation represents a feasible therapeutic approach for the treatment of ALCL (24). The intact ALK kinase domain within EML4-ALK possesses marked transforming as well as oncogenic activity in vitro and in vivo, respectively (12,21,25).…”
Section: Introductionmentioning
confidence: 80%
“…To analyze the effects of NPM-ALK expression in its native cellular background (ALCL), we used an inducible RNAi approach capable of silencing the expression of NPM-ALK fusion protein in ALK-positive cells. We have previously shown, using a constitutively expressed shRNA construct and small-molecule approach, that ALK expression is strictly required for the survival of ALK-positive ALCL cells in vitro and in vivo (11,12). Here, we have further exploited this tool to generate ALK-positive cell lines expressing a doxycycline-inducible ALK shRNA.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the constitutive expression and phosphorylation of NPM-ALK are sufficient for cellular transformation in vitro and for the development of lymphoid neoplasia in transgenic mice (10). Moreover, ALK activity is strictly required for the survival of ALCL cells in vitro and in vivo (11,12). However, the precise mechanisms by which NPM-ALK mediates cellular transformation and its requirements for tumor growth and survival are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three constructs were cloned (BamHI-SalI) in pCCL.sin.PPT.hPGK.GFPWpre (kindly provided by L. Naldini, San Raffaele Institute, Milan, Italy) replacing the GFP cassette. High titer lentiviral vector stock was produced in HEK-293T cells by Effectene cotransfection of the plasmid with the packaging vectors pMDLg/pRRE, pRSV-Rev and pMD2.VSVG [46]. Supernatants were collected and concentrated by ultracentrifugation.…”
Section: Lentivirus Production and Cell Infectionmentioning
confidence: 99%